The Impact of Preprinted Antibiotic Order Forms on Vancomycin and Carbapenems Consumption: Effect of Antibiotic Order Forms on Vancomycin and Carbapenem Usage - Forouhi, Mahtab; Pourheidar, Elham; Haghighi, Mehrdad; Alavi-Moghaddam, Mostafa; Nabavi, Mahmood; Shoaei, Simindokht; Farahbakhsh, Mohammad; Hadavand, Fahimeh; Sistanizad, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2024)
According to the increasing trend of antibiotic consumption all over the world, a rising concern is the emergence of resistant pathogens due to the inappropriate use of antibiotics, which increases the risk of treatment failure and mortality. Antibiotic Order Form (AOF) is an antimicrobial stewardship program protocol recommended to improve rational antibiotic use. We aimed to compare the antibiotic consumption rate, i.e., vancomycin and carbapenems, before and after preprinted AOFs were implemented. This study also evaluated physicians' compliance with AOFs as a secondary outcome. This prospective descriptive study was conducted from July to December 2015 in a 570-bed teaching hospital in Tehran, Iran. AOF includes demographics, microbiological, and clinical data on infection designed for vancomycin and carbapenems, including imipenem and meropenem. Prescribers were asked to fill out predesigned forms after prescribing the selected antibiotics and deliver them to the pharmacy on July 1, 2015. Collected data during this 6-month study period were compared with the same period times years 2011 to 2016 (4 years before and one year after implementation of AOF) to determine the effect of AOFs on the selected antibiotics consumption that had been calculated based on Daily Doses per 100-patients day (DDD/100-bed days). This study showed that although vancomycin had an increasing trend from 2011 to 2014, implementing the AOF program could stop this trend in 2015. vancomycin consumption significantly decreased compared to the previous year (P = 0.039). This effect of the program was not the same on the use rate of carbapenems, and their use was increased nonsignificantly in 2015 (P = 0.606). The acceptance of prescribers in filling out the forms for vancomycin increased from 5.12% in the first month to 57.75% in December. This increase was from 4.20% to 37.26% for carbapenems. According to the increasing trend of antibiotic consumption in hospitals, we recommend improving utilization surveillance of antibiotics by choosing an appropriate antibiotic, optimal dosing, and desired duration of treatment that are important in decreasing the risk of developing resistant microorganisms due to misuse. The forms are much more effective when accompanied by the acceptance of prescribers.